Electronic reports as a proposed tool to facilitate some of the tasks of educational supervisors in Wadi Al- Duwaser province and their attitudes towards it - Alshotif, Ibrahim Mohammed (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the extent to which educational supervisors accept electronic reports as a suggested tool to facilitate some of their tasks and their attitudes towards them in Wadi Al- Dawasir Governorate. To achieve this goal, the study used descriptive survey, And The questionnaire as a tool included (78) items distributed over nine domains, It was distributed to all members of the study population (all educational supervisors in the Department of Education in Wadi Al- Dawasir Governorate), which were (27) supervisors. The study concluded that the educational supervisors’ attitudes towards working with electronic reports for educational supervision obtained a total average of (2.80 out of 3), meaning a (very high) degree of orientation. The most prominent positive attitudes of educational supervisors towards working with electronic reports for educational supervision are: smooth access to reports, the ability to access them through mobile, and filling out forms easily, and working with electronic reports contributed to the organization of their supervisory work and facilitated workflow, and there were no problems in Fill out the forms, and the sufficiency of the data contained therein. Through the results of the study, the researcher recommended adding other data to a number of electronic forms to improve them, which are models: the supervisory visit, the school leadership supervisor’s visit, the administrative visit, training programs (the trainer and the trainee), improving the electronic reporting site in terms of design and colors, and ease of browsing from the smartphone.